Quantum electrodynamics divergencies - Nicola Fabiano (University of Defence in Belgrade, 2021)
Introduction/purpose: The problem of divergencies in Quantum Electrodynamics (QED) is discussed. Methods: The renormalisation group method is employed for dealing with infinities in QED. Results: The integrals in QED giving physical observables are finite. Conclusions: The divergencies in QED can be treated in a consistent way providing mathematical rigorous results.